2012
DOI: 10.1002/srin.201200157
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Fast Cooling of a Hot Steel Plate by Using High Mass Flux Air Atomized Spray

Abstract: In the current research, the ultra fast cooling (UFC) of a hot stationary AISI‐304 steel plate has been investigated by using air atomized spray at different air and water flow rates. The initial temperature of the plate, before the cooling starts, is kept at 900°C or above. The spray was produced from a full cone internal mixing air atomized spray nozzle at a fixed nozzle to plate distance; and the average spray mass flux was varied from 130 to 370 kg m−2 s by selecting different combinations of air and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 16 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…The set-up mainly consists of a cooling section with nozzle arrangement, a data acquisition system, an air loop and water coolant circuits which supply the air and coolants to the nozzle and a recycling coolant circuit to the liquid reservoir. The flow rates of air and water are 30 m 3 /hr and 10 l/min respectively maintained throughout all the experiments, which have been optimized earlier for the current experimental set-up [14]. The test plate used is AISI 304 designated stainless steel of dimensions 100 mm × 100 mm × 6 mm, and is arranged 60 mm below the nozzle orifice for cooling.…”
Section: Experimental Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The set-up mainly consists of a cooling section with nozzle arrangement, a data acquisition system, an air loop and water coolant circuits which supply the air and coolants to the nozzle and a recycling coolant circuit to the liquid reservoir. The flow rates of air and water are 30 m 3 /hr and 10 l/min respectively maintained throughout all the experiments, which have been optimized earlier for the current experimental set-up [14]. The test plate used is AISI 304 designated stainless steel of dimensions 100 mm × 100 mm × 6 mm, and is arranged 60 mm below the nozzle orifice for cooling.…”
Section: Experimental Facilitymentioning
confidence: 99%
“…However, the method of achieving UFC is hardly disclosed and large amount of liquid coolant used is another drawback for the environmental and economic constraints of industries [10]. Mohapatra et al [14] found the easier way to get the ultrafast cooling on a 6 mm thick plate using high mass flux air-atomized water spray system and it was further enhanced by using inclined spray impingement by Ravikumar et al [15]. During the process of spray cooling of high temperature surfaces, the droplets cannot completely evaporate.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra‐fast cooling is realized with water jets and/or water/air jets in metal processing. This phenomenon is important for the controlled cooling of plates, 6xxx grade aluminum and ultra‐high strength steel strips.…”
Section: Continuous Annealing and Galvanizing Linesmentioning
confidence: 99%
“…The dendrite size and center shrinkage cavity are developed as a result of the slow cooling conditions. The cooling rate is key to the quality of M2 steel [19] and an appropriate cooling rate has a positive effect on relieving internal defects in the billet such as cracks and center shrinkage cavities [20,21].…”
Section: Introductionmentioning
confidence: 99%